Whaia te tika : Hato Paora College, the first fifty years : a thesis as part fulfilment of the requirements for the MA Degree, Massey University - Lawton, Tata R (Massey University, 1996)
This thesis is about the context within which Hato Paora College has developed. The study explores the establishment of a Māori Church boarding school was established and its relevance to Maori developmental needs within an environment of religious patronage. The thesis attempts to link the evolution of Hato Paora with changing policies of Māori, the Church and the State. Examined within a two dimensional framework are the contributions made by each Rector in regards to governorship and administration, curriculum, religion, taha Māori, extra-curricular activities, cadets, old boy's association, community, amenities and, the farm. The Rector-centred approach enabled a systematic explanation of the College performance and the often contradictory expectations of staff, pupils and the wider Māori community. Literary research, interviews, and a questionnaire were used to gather the appropriate information. The thesis concludes that Hato Paora College has played a significant role in preparing Māori to assume positive roles in a changing society, but cautions that future contributions may require fundamental changes if the College is to remain relevant in the 21st century.
Keywords: Kōrero nehe; Kura tuarua; Hāhi Karaitiana; Secondary education